2002
DOI: 10.1007/s005950200198
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Cardiac hydatid cysts are extremely rare and, although patients may remain asymptomatic for many years or have only minor nonspecific symptoms, they are associated with life-threatening complications. We report the case of a 32-year-old woman with an acute arterial embolism caused by a ruptured hydatid cyst in the heart. An emergency operation revealed that the embolism originated from the left cardiac chamber caused by a cyst in the left ventricle. There were also three cystic lesions in the right lung. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 9 publications
1
2
0
1
Order By: Relevance
“…Cardio-pericardial hydatid cysts, similar to those of our patient, are usually visible in the majority of plain-chest radiographic findings [ 28 , 33 , 34 , 35 , 36 , 37 ]. The typical image is that of an addition that is well limited, having clear edges.…”
Section: Discussionsupporting
confidence: 80%
“…Cardio-pericardial hydatid cysts, similar to those of our patient, are usually visible in the majority of plain-chest radiographic findings [ 28 , 33 , 34 , 35 , 36 , 37 ]. The typical image is that of an addition that is well limited, having clear edges.…”
Section: Discussionsupporting
confidence: 80%
“…Odev et al [16] and Lahdhili et al [17] documented that, due to the effect of pump, the left ventricle cysts perforated in the aorta but the right ventricle cysts perforated intracavitary. Unlu et al [18] and Kopp et al [19] showed that the incidence of intracardiac perforation is between 20-40% and after a cyst perforation 75% of the patients died from septic shock or embolic complications.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of intracardiac perforation is very high (25-40%). After cyst perforation 75% of the patients died from septic shock or embolic complications [9,10]. …”
Section: Discussionmentioning
confidence: 99%